2020
DOI: 10.1002/eng2.12245
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory‐scale simulation of industrial neutral electrolytic pickling as a bipolar system—Parameters affecting indirect polarization pickling of annealed stainless steel

Abstract: As the production of stainless steel increases, environmental concerns due to an increasing demand of production capacity, require an efficient use of energy and materials. Efficient removal of otherwise slow-to-dissolve chromium oxide layer can be achieved with electrochemical pre-pickling before final mixed acid pickling. Neutral electrolytic pickling can be used to rapidly dissolve chromium oxides but suffers from low current efficiency of both the reaction and the system. In order to study the effect of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…When the applied external voltage was 5-15 V, it was calculated that only 40-50% of the steel strip's surface was sufficiently polarized. This value is within the range of previous studies, which indicated 40% from direct measurements of the current [32] and 60-65% calculated by mathematical modeling [39]. The loss of potential was mainly due to the electrolyte's resistance.…”
Section: Multiphysics Modelingsupporting
confidence: 85%
See 2 more Smart Citations
“…When the applied external voltage was 5-15 V, it was calculated that only 40-50% of the steel strip's surface was sufficiently polarized. This value is within the range of previous studies, which indicated 40% from direct measurements of the current [32] and 60-65% calculated by mathematical modeling [39]. The loss of potential was mainly due to the electrolyte's resistance.…”
Section: Multiphysics Modelingsupporting
confidence: 85%
“…Figure 10 shows that, even though the electrolyte's properties did not affect the polarization behavior of the electrodes (as shown in Figure 7), a significant part of the polarizing power was lost to the electrolyte's resistance. Nevertheless, the calculated current densities were within the industrial levels of 500-3500 A m −2 reported in numerous studies [31,32,40].…”
Section: Multiphysics Modelingsupporting
confidence: 78%
See 1 more Smart Citation